LEVEL OF PASSING SKILLS IN FOOTBALL GAMES IN SD NEGERI 40 KOTA BENGKULU - M Rendra Wahyudhy; Dolly Apriansyah (Perkumpulan Dosen Muda Bengkulu, 2020)
This study aims to determine the level of Passing Skills in Football Games at SD Negeri 40 Bengkulu City. This research method is quantitative descriptive. The population of this study was all 30 students of Grade V of SD Negeri 40, Bengkulu City. Samples were taken using a non-probability sampling method. In addition, the sampling was done by Accidental Sampling (Convenience sampling). alone who accidentally met with researchers can be used as a sample. So that in this study included in the Accidental Sampling are grade V students of SD Negeri 40 Bengkulu City with a total of 30 students. Then the sample in this study is the entire population so that the sample numbered 30 students and female students. The results of the data analysis showed that: The level of passing skills of students and students in football games at SD Negeri 40 Bengkulu City, namely there are two percentage results, first the level of passing skills students and students are at intervals of 25-30, namely the category